Problem-Based Learning Model (MONAKI) to Improve Motivation and Learning Outcomes of Pekanbaru STT Students: Model Pembelajaran Berbasis Masalah (MONAKI) Untuk Meningkatkan Motivasi dan Hasil Belajar Mahasiswa STT Pekanbaru - Tri Monarita Johan; Raimon Efendi (International Journal of Technology Vocational Education and Training, 2024)
A learning model is a systematic approach or framework used to design, implement and evaluate the teaching and learning process. The purpose of using learning models is to increase the effectiveness of teaching and facilitate the achievement of predetermined learning goals. This type of research is Classroom Action Research (PTK) with a qualitative approach consisting of two cycles with each stage, including the planning stage, implementation stage, observation stage and reflection stage. The research location was carried out at the Pekanbaru College of Technology, Electrical Engineering study program with a total of 35 sixth semester students. The results of data analysis from observations on the learning motivation of semester 6 students, especially in the Computer Applications in Electrical Power Systems course in the application of the problem-based learning model with MONAKI syntax, the indicator of student learning motivation with the lowest level of success, namely in the 1st cycle, is the indicator of having a goal to be achieved. (60%) and in the second cycle it is an indicator of being diligent and thorough (85.71%). From the data above, it was found that the average post test score had increased by 48.57% from the minimum completeness criteria in implementing the Problem-Free Learning Model (MONAKI). The application of the Problem Based Learning Model (MONAKI) in the Computer Applications in Electrical Power Systems course, semester VI, has proven to be helpful in developing students' motivational abilities and learning outcomes.